The emergence of volcanic oceanic islands on a slow‐moving plate: The example of Madeira Island, NE Atlantic. (24th February 2015) - Ramalho, Ricardo S.; Brum da Silveira, António; Fonseca, Paulo E.; Madeira, José; Cosca, Michael; Cachão, Mário; Fonseca, Maria M.; Prada, Susana N.
Abstract The transition from seamount to oceanic island typically involves surtseyan volcanism. However, the geological record at many islands in the NE Atlantic—all located within the slow‐moving Nubian plate—does not exhibit evidence for an emergent surtseyan phase but rather an erosive unconformity between the submarine basement and the overlying subaerial shield sequences. This suggests that the transition between seamount and island may frequently occur by a relative fall of sea level through uplift, eustatic changes, or a combination of both, and may not involve summit volcanism. In this study, we explore the consequences for island evolutionary models using Madeira Island (Portugal) as a case study. We have examined the geologic record at Madeira using a combination of detailed fieldwork, biostratigraphy, and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjbwbrm2n" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />40Ar/39Ar</alternatives> geochronology in order to document the mode, timing, and duration of edifice emergence above sea level. Our study confirms that Madeira's subaerial shield volcano was built upon the eroded remains of an uplifted seamount, with shallow marine sediments found between the two eruptive sequences and presently located at 320–430 m above sea level. This study reveals that Madeira emerged around 7.0–5.6 Ma essentially through an uplift process and before volcanic activity resumed to form the subaerial shield volcano. Basal intrusions are a likely uplift mechanism, and their emplacement is possibly enhanced by the slow motion of the Nubian plate relative to the source of partial melting. Alternating uplift and subsidence episodes suggest that island edifice growth may be governed by competing dominantly volcanic and dominantly intrusive processes.